Re-defining Informal Employment and Measuring its Determinants: Evidence from Russia - Hartmut Lehmann; Anzelika Zaiceva (Institute for the Study of Labor (IZA), 2013)
Informal activities impact countries' economic development and overall growth. However, studying informal employment is not easy and it is crucial to provide a valid definition of it. This paper contributes to the recent discussion of the measures of informality by taking advantage of a rich dataset on Russia over the period 2003 - 2011, that is before and after the economic downturn, together with a special supplement on informality that allows to construct different measures of informal employment and to analyze its determinants. We demonstrate that the incidence of informal employment varies across the different definitions. However, the determinants of informal employment are roughly stable across the different measures as long as we exclude firm size as a criterion. We also show that risk-averse individuals, as expected, are less likely to select themselves into informal employment.
Keywords: J31; J40; P23; 330; informal employment; definitions; incidence; determinants; Russia